The response of tax bases to the business cycle: the case of Alberta - Ferede, Ergete (My University, 2013)
One major concern that policy makers face is whether they can plan their future tax receipts and spending in a predictable manner. In the absence of tax rate changes, tax revenue volatility arises due to volatility of tax bases. In the face of fluctuations in economic activity, the amount of tax revenue that a provincial government collects depends on how the various tax bases respond to the business cycle. We investigate the relationship between the business cycle—measured by the deviations of Gross Domestic Product from its long-run trend—and Alberta’s major tax bases for the period 1976–2008. Our analysis indicates that the Alberta’s corporate income and sales tax bases show the most and least responsiveness to the business cycle. The policy implication of this is that, if the objective of the Alberta government is to have less volatile and somewhat reasonably predictable tax revenue sources, diversifying its tax bases to include sales tax looks promising.
Keywords: taxes; public economics; Alberta